Cover Image, Volume 74, Issue 3. Issue 3 (March 2017) - Muñoz‐Llancao, Pablo; de Gregorio, Cristian; Las Heras, Macarena; Meinohl, Christopher; Noorman, Kevin; Boddeke, Erik; Cheng, Xiaodong; Lezoualc'h, Frank; Schmidt, Martina; Gonzalez‐Billault, Christian
Abstract : The cover image, by Pablo Muñoz‐Llancao et al., is based on the Research Article Microtubule‐regulating proteins and cAMP‐dependent signaling in neuroblastoma differentiation, DOI:10.1002/cm.21355 .